Graded assessment of pupils’ conduct as a research object . Discovering a hidden school upbringing curriculum - Jaskulska, Sylwia (Uniwersytet Zielonogórski and Wydawnictwo Adam Marszałek, 2013)
In the text, I raise the issue of a hidden curriculum. I refer myself to the course and results of my own research concerning marking pupils’ conduct at lower secondary schools and I look for answer to the question: What is the content of the hidden curriculum of the schools that I conducted my research at? In order to answer this question, I start by quoting the research results, I refer myself to the course of the research and fi nally I make an att empt at interpreting the research material gathered within the fame of this article.
Ocenianie zachowania uczniowskiego na stopień jako przedmiot badań. Odkrywanie ukrytego programu szkoły
Keywords: hidden school upbringing curriculum; graded assessment of conduct